(untitled) (Economic and Political Thought, 2013)
According to the authors, the major direct threats that undermine the present-day capitalism are the weakness of state institutions and, as a result, defects of market regulations on the one hand, and market deformations connected with the loss of appropriate self-regulation of particular markets, especially the financial one, on the other hand. The authors believe that the substantial reason of those threats lies in the sphere of the political system transformation. With the use of the political doctrines set, in the middle of which there is the economic liberalism based on the philosophic liberalism, the authors point out the consequences of the transformation in the USA after 1980, followed by Europe and Poland from the very beginning of the transformation, and other states, to the system called neo-liberalism. In the authors’ opinions, the best solution for the world would be a re-entry into the liberal system, in which the relations between the state and markets would be of a cooperative character making it possible to achieve synergic effects.